New Public Management Reforms and the Performance of Public Enterprises: An Assessment of Privatization in Nigeria's Telecommunications Sector - Adejuwon, David; Amodu, Akeem; Majekodunmi, Aderonke (African Journal of Politics and Administrative Studies, 2024)
The implementation of New Public Management (NPM) reforms, particularly privatization, has been a significant strategy adopted by governments worldwide to enhance the performance of public enterprises. This article focuses on the telecommunications sector in Nigeria, where privatization was introduced as part of broader economic reforms in the early 2000s. The objective is to assess the influence of privatization on the performance of public enterprises within this sector. The article is anchored on public choice theory. It is qualitative in nature, relying on secondary sources of data, such as, journals, textbooks, official publications and internet materials. It observes that privatization of public enterprises in the telecommunication sector in Nigeria has led to improvements in operational efficiency, increased investment inflows, and expanded service coverage. However, challenges such as regulatory effectiveness, equity in service provision, and the socio-economic impact on marginalized populations remain significant concerns. It contributes to the broader discourse on NPM reforms by providing empirical insights into the complexities and outcomes of privatization within Nigeria's telecommunications sector. It concludes with policy recommendations aimed at optimizing the benefits of privatization while addressing its associated challenges to ensure sustainable and inclusive growth in the sector.
Keywords: New Public Management; Operational Efficiency; Privatisation; Public Enterprises; Public Sector Performance; Service Delivery

SME contractors’ management practices to achieve sustainable business performance in the Eastern Cape province, South Africa - Sogaxa, Athenkosi (Acta Structilia, 2024)
The construction industry in the Eastern Cape province of South Africa plays a crucial role in the region’s economy, yet small and medium enterprise (SME) construction companies face significant challenges in achieving long-term business sustainability. This article aims to provide practical guidelines for SMEs, by investigating the most critical construction management practices adopted by SME contractors. Utilising a quantitative approach, data were collected from 59 purposefully selected participants, including directors, construction managers, quantity surveyors, site agents, and technicians, all registered under the Construction Industry Development Board (CIDB) Grades 1-4 in General Building (GB). The management practices of SME contractors were analysed using the relative importance index (RII) and factor analysis to rank these practices according to their significance. Findings indicate that SME contractors prioritise health and safety strategies, effective resource utilisation, integrated project management systems, competent recruitment, strong leadership skills, and robust health and safety management as essential practices. The principal component analysis identified six key management factors to enhance competitiveness while contributing to the region’s sustainable development goals. These factors include shared knowledge among management, effective project scope planning, comprehensive health and safety management, ownership of construction business knowledge, scope control on projects, and clearly defined goals for management teams. This study is original in its focus on the specific management practices that can strengthen the sustainability of SME contractors within a developing region, providing a valuable framework for enhancing their operational effectiveness.

Digital Vulnerability and the Formulation of Harmonised Rules for Algorithmic Contracts: A Two-Sided Interplay - Rodriguez, Teresa de Las Heras Ballell (The New Shapes of Digital Vulnerability in European Private Law, 2024)
This book provides an analysis on whether and how the current European legal framework adequately deals with personal conditions in which digital...

Termination of the Mandate of an Agent: An Examination under OHADA Uniform Act on General Commercial Law - Ndekwena Noh, Alison (Scholars International Journal of Law Crime and Justice, 2024)
When an agency relationship is created, it confers on the parties obligations which must be fulfilled by the parties. These obligations do not remain forever as they can come to an end. This can be done under normal circumstances by the act of the parties or by operation of the law and when the conduct of the agent is in contradiction to the mandate agreement as may be the case if the agent is liable for serious misconduct as provided by the OHADA Uniform Act on General Commercial Law. The provisions of the act regarding termination on grounds of serious misconduct is worrisome, as the act talks about termination in such manner only for commercial agents and is silent about the other two types of agents: the broker and the commission agent. The act also, does not tell us what this serious misconduct it mentions by the commercial agent is, nor gives us insights on what constitutes such conduct to warrant termination of the mandate of the agent by the principal. When termination of the agency is done under conditions as such, it has grave consequences on the agent who might not be entitled to certain benefits associated with termination of the contract such as loss of the right to compensatory allowance or indemnity and more importantly may give room to arbitrary or wrongful termination of the mandate of the agent. Through analytical and comparative studies, this paper focuses on termination of the mandate of an agent under the OHADA Uniform Act on General Commercial Law, wherein, the different modes of termination of the mandate of an agent have been discussed, and more specifically makes an attempt in looking at what serious misconduct is and what could amount to such conduct so as to avoid arbitrary or wrongful termination. It is therefore suggested that, statutory guidelines found in other statutes in relation to the subject matter can serve as a lamp light in our context.
OpenAlex: https://openalex.org/W4403198358
Keywords: Mandate

Editorial on Doing business in Africa: Navigating opportunities and challenges in Africa's emerging markets - Adomako, Samuel; Shenkar, Oded; Liu, Xiaohui; Amankwah-Amoah, Joseph; Ahsan, Mujtaba (Journal of International Management, 2024)
This editorial delves into the evolving context of doing business in Africa, tracing its journey from being dubbed the “hopeless continent” to becoming a beacon of hope and opportunity. Drawing on a wealth of scholarly research, it highlights Africa's increasing attractiveness for global investments, underscored by rising FDI inflows and the emergence of a vibrant middle class. Despite these promising trends, the editorial also sheds light on the persistent challenges, including institutional fragility and political instability, coupled with limited representation in the existing international business discourse. We advance a more nuanced understanding of Africa's business environment, emphasizing the need for responsible growth, improved governance, and sustainable development. Thus, the Special Issue offers insights into the complexities and challenges of doing business in Africa, as well as the paradoxes and potential for fostering competitiveness and inclusive growth on the global stage.
Keywords: Africa; Doing business; International business; MNEs

Joint and several liability at the interface of national and international law and the FIDIC conditions of contract - Mahasneh, Nisreen (Uniform Law Review, 2024)
The international terms of the 2017 FIDIC Red Book (reprinted and amended in 2022) state that, when the contractor is a joint venture (JV), all members are jointly and severally liable to the employer. These terms also establish certain procedural rules—the most important ones being the submission to the employer of the JV undertaking and the appointment of a leader. However, these international terms do not provide for substantive rules pertaining to the plurality of the JV members. These require reference to the applicable law that governs the construction contract. The applicable law can be domestic law, such as Qatari law, or an international soft law, such as the Unidroit Principles. Comparing these two possibly applicable laws, it becomes evident that there are no significant differences between the two regarding the substantive rules concerning a plurality of obligors. Furthermore, it is argued that the majority of these substantive legal rules, whether national or international, are inoperative in a construction contract incorporating the international terms of the FIDIC Red Book.

Termination of Commercial Sale Contracts under the OHADA Uniform Act Relating to General Commercial Law - Ataíde, Rui; Boura, Marta (Centro de Investigação de Direito Privado (CIDP) Research Paper, 2024)
The Uniform Act relating to General Commercial Law of the Organisation for Harmonisation of Business Law in Africa (hereinafter referred to as the OHADA Uniform Act) establishes a commercial sale regime applicable to any trader (natural or legal person), including any commercial companies whose place of business or registered office is located in the territory of a party to the Treaty on the Harmonisation of Business Law in Africa. In this study we propose to analyse the non-performance of commercial sale agreements, focused on its termination regime, by reflecting on the right of termination, the termination by judicial means, its grounds, exemption from liability and the effects of termination. The economic and legal relevance of the commercial sale contract justifies the opportunity to reflect on how legal standardisation process has been achieved overall, particularly with regard to termination regimes. Both OHADA Uniform Act and the Vienna Convention on Contracts for the International Sale of Goods of 1980 (CISG) were conceived as unification mechanisms to circumvent the constraints and legal uncertainty associated with cross-border trade. Therefore, this analysis aims to assess how OHADA rules embody the long process of evolution in French law, as well as the influence of the CISG.
Keywords: CISG; Commercial sale contracts; Comparative law; French law; International Organisations; Legal standardisation; OHADA; Portuguese law; Termination regime; Uniform Act relating to General Commercial Law for Harmonisation of Business Law in Africa

Sustainable development clauses in international contracts through the lens of the Unidroit principles - Pannebakker, Ekaterina (Uniform Law Review, 2024)
Most transactions that leave an imprint on the environment and communities are organized by commercial contracts. However, little is known about the way in which parties reflect sustainable development in contractual clauses. How can parties to international contracts commit to respect sustainable development goals? What are the possible degrees of commitment? Which contractual mechanisms can apply to the monitoring of compliance? How does one establish a link between the failure to meet sustainable development goals and the contractual liability or termination of contract? This article identifies contractual clauses relating to sustainable development and analyses these clauses through the lens of the 2016 International Institute for the Unification of Private Law (Unidroit) Principles of International Commercial Contracts (PICC). Drawing inspiration from open access contracts, the analysis will demonstrate that Article 1.8 of the PICC, precluding inconsistent behaviour, and Articles 5.1.4 and 5.1.5, on the duty of best efforts and the obligation to achieve a specific result, as well as the provisions on liability, can assist contract drafters, judges, and arbitrators in drafting and interpreting such clauses.

Mobile money and financial inclusion in Africa: Emerging themes, challenges and policy implications - Osabutey, Ellis L. C.; Jackson, Terence (Technological Forecasting and Social Change, 2024)
Mobile money is purported to promote financial inclusion. The growing number of studies have largely focused on transactions and related benefits with limited attention to emerging challenges, policies and initiatives that address the relative needs of different stakeholders. Consequently, little has been done to probe the ‘bottom-of-the-pyramid’ paradigm that underpins these assumptions. There has been inadequate endeavour to examine ways that empirical research could shed more light on these challenges and how to overcome them. To address these gaps, this study reviews the emerging literature on mobile money that explores both benefits and challenges. From our study three main themes emerge that suggest areas where challenges to the efficacy of the mobile money-financial inclusion link still appears not to have been adequately addressed by policymakers: ensuring integrity, privacy and security; addressing resource and infrastructure constraints; and integrating stakeholder benefits. Yet we suggest merely addressing these challenges does not go far enough in safeguarding the needs of local communities, as major stakeholders. Evidence from our study suggests little direct benefit to the poorer sections of local communities, only to the strata above and to elites and external stakeholders. This has implications for development and social change through technology adoption.
Keywords: Africa; Bottom-of-the-pyramid; Financial inclusion; Fintech; Mobile money

Transborder flow of personal data (TDF) in Africa: Stocktaking the ills and gains of a divergently regulated business mechanism - Babalola, Olumide (Computer Law & Security Review, 2024)
Technology-based transactions are inseparable from the routine exchange of data. These exchanges may not pose privacy problems until the movement takes extra-territorial turns thereby facing multiple levels of cross-border regulations. In the 80 s, the frequency of transfer of personal data beyond geographical boundaries in Europe precipitated the regulation of transborder data flows (TDF) beginning with the enactment of the Organization for OECD Guidelines. In Africa, the concept of TDF is more complex than usually viewed by the stakeholders and this is partly because neither the African Union nor other regional bodies have introduced legislation on TDF. Like many concepts in data protection, TDF is bereft of a generally accepted meaning. Regardless of the uncertainty, this paper approaches TDF as the transmission of personal data from one country to another country or international entity for the purpose of processing. The paper discusses some definitions of TDF as understood under African regional and national data protection legislation. In a comparative and normative approach, the paper analyses the barriers to TDF in Africa vis a vis the European experience and then concludes with recommendations for workable TDF within and outside the continent from an African perspective beginning with the harmonization of existing regional framework.
Keywords: Africa; Data Protection; ECOWAS; GDPR; Privacy; Transborder data transfer

Influence of remuneration on organizational performance in co-operative banks in Kiambu, Kenya - Brian, Kasale; Abuga, Isaac Mokono (African Journal of Social Issues, 2024)
This study investigates the influence of remuneration on organizational performance in cooperative banks in Kiambu County, Kenya. Employing a mixed-methods approach, the research explores how compensation packages, salary reviews, and employee recognition impact performance. The study utilizes a descriptive research design with structured questionnaires to gather data from 94 participants. Findings indicate a significant correlation between competitive remuneration and enhanced organizational performance. The majority ofemployees are satisfied with salary increments and recognize the positive effects of frequent salary reviews on their motivation and job satisfaction. The study also highlights the importance of recognition and praise in boosting employee morale and engagement, contributing to overall organizational success. This research is grounded in Equity Theory, which posits that fair treatment in compensation leads to higher motivation and productivity. The conclusions drawn suggest that cooperative banks should implement equitable and competitive remuneration strategies, along with regular salary reviews and robust recognition programs, to enhance performance. The study provides valuable insights for policymakers andbank managers aiming to improve organizational effectiveness through strategic human resource practices.
Keywords: Co-operative Banks; Employee Motivation; Equity Theory; Organizational Performance; Remuneration

Articulation between Soft Law and Hard Law in the Award of Public-Private Partnership Contracts through Unsolicited Bids in Burundi: Towards Harmonization with International Practice - Amani, Jean Pierre (Open Journal of Social Sciences, 2024)
The awarding of public-private partnership (PPP) contracts through unsolicited bids is characterized by flexible domestic law, with the involvement of public and private players aiming to achieve the general interest objective of public infrastructure development and, by extension, national development. These players are helping to build the normative framework for PPP project activities by spontaneous offer, given their increasingly widespread use on the bangs of positive law, while their standards are classically deprived of the binding force attached to hard law. Marked by its normative guarantee, the flexible law of unsolicited bids is situated at the threshold of the mandatory, and is essential to PPP law. It produces legal effects by linking up with the hard law of PPP contracts, which is the law of the parties. This link between soft law and hard law has a major legal impact on the transformation of the law and legal certainty, for the benefit of investment confidence, especially international investment confidence. Faced with the limitations of positive law on the award of PPP contracts in unsolicited bids, and the difficulties of interpreting soft law and hard law standards, there is a need for harmonization with international practice. To this end, the instruments of the United Nations Commission on International Trade Law (UNCITRAL) on PPPs are being used to link up with Burundian hard law through a transposition mechanism. It is therefore possible that our positive approach to PPP contracting could be improved, highlighting the principle of competition and the exception of non-competition, while taking into account the win-win principle, risk sharing and performance. Finally, the article considers the adjustments to the hard law that would be necessary if Burundi were to decide to revisit the legal framework to make it more attractive to investment, and thus ensure the completion and financing of PPP contracts by spontaneous bidding.
Number: 1
Keywords: Articulation of Law; Competition Principles; Hard Law; Harmonization Principles; Legal Certainty; Mutation of Law; Soft law; Spontaneous Offer

The International Tax Regime Complex: Understanding Change in Global Tax Governance - Kuhn, Katharina; Cadzow, Lucinda; Heitmüller, Frederik; Hearson, Martin; Randriamanalina, Tovony (Institute of Development Studies, 2024)
Keywords: Global tax governance; International tax; Legitimacy; Low-income countries; Regime complex; UN Framework Convention on International Tax Cooperation

Digitization and sustainability: Practical convergences of two leading discussions in business law - Mittwoch, Anne-Christin (Beiträge zum Transnationalen Wirtschaftsrecht, 2024)
Until now, digitization and sustainability have stood side by side in the discussion of business law. As leading discourses of the present-day business scene, both topics are leading to profound change in companies and are influencing each other in the process - a circumstance that can no longer be ignored by corporate management. The article shows the guiding ideas behind both discussions, as well as their convergences and interactions, and asks about the effects they have on management's duty to act.
Keywords: Corporate Digital Responsibility; Corporate Sustainability; Digitization; Directors' Duties; Sustainability

Chapter 1, Introduction to contract law and theory - DiMatteo, Larry A. (Principles of Contract Law and Theory, 2023)
This chapter provides background information on the evolution of the common law of contracts. It begins with a short history of the evolution of the common law in England including the roles played by the Roman Catholic Church, the development of a dual court system—one in law and the other in equity, the transition from absolute monarchy to a parliamentary form of government, the creation and restrictiveness of the English writ system, the common law’s reception in America, and the building of a general law of contract in the nineteenth century. It explains the historical differences between law and equity, along with the fusion of the two into a single court system. It also discusses the justifications given for contract law and its role in society. It describes the different perspectives of written or formal law, theory, and practice, and importantly, the difference between law in the books versus law in action. Finally, it explains the differences between rules, principles, and standards, and the boundaries of contract relative to other areas including tort and unjust enrichment.

Business climate and global value chains: Insights from Africa - Ajide, Folorunsho M. (Transnational Corporations Review, 2023)
This paper provides insights on how business climate affect global value chains (GVC) participation in the panel of African nations. The study explores country-level data spanning over a period of 2006–2018. Using the novel method of moments (MM)-Quantile regression, system generalized methods of moments (SYSGMM) and Panel spatial consistent correlation (PSCC) techniques, the study finds that all aspects of business environment have significant impacts on GVC participation in Africa. In specific, information and communication facilities, getting electricity, getting credit, trading across border, enforcing contract, protecting investors and business start-up registration have positive and significant impact on GVC. We also discover that tariff reduces GVC participation while strong political institutions enhance participation. The study concludes that business environment factors are fundamental to ensure high level of GVC participation. Political institutional framework needs to be strengthened to further encourage GVC participation in Africa.
Keywords: Africa; Business environment; Climate; GMM; Global value chains

Terms of trade, governance and household income in selected African countries - Edeme, Richardson Kojo; Mumuni, Sulemana (Sustainable Futures, 2023)
As African countries grapple with the challenges of terms of trade occasioned by economic uncertainty, there is a need for a study on the effect of terms of trade on household income in Africa. Also, as African countries continue to commit to the role of institutional quality in improving terms of trade, this study further reinforces the role of governance on household income in Africa. The study employs the Two-stage Least Squares (2SLS) fixed effects estimation technique based on data spanning 2002–2021 for 36 selected African countries. This study provides more robust evidence by employing household final consumption expenditure as a measure of household income. Findings suggest that improvement in the terms of trade stimulates household income. Similarly, the results indicate that governance plays a critical role in enhancing household income status in Africa. Specifically, government effectiveness, control of corruption, regulatory quality, rule of law, and political stability positively and statistically significantly influence household income levels in Africa. Furthermore, GDP per capita growth positively impacts household income, albeit the effect is statistically insignificant. On the contrary, higher inflation rates, exchange rate volatility, and foreign direct investment (net inflows) have a limiting effect on household income, although, the effect of currency depreciation is generally not statistically significant. Sequel to these findings, the study calls for strong institutional quality and export promotion strategies in Africa.
Keywords: 2SLS; Governance; Household income; Terms of trade

South African controlled foreign companies' rules and the digital economy - Sengwane, Khodani (Potchefstroom Electronic Law Journal, 2023)
South Africa's controlled foreign company ("CFC") rules were enacted more than two decades ago before most of today's business models existed. These are anti-avoidance rules that ensure the South African taxation of profits diverted offshore by South African residents. In terms of the CFC rules, the profits of a non-resident company may also be subject to tax in South Africa at the hands of its South African resident shareholder if such non-resident company is considered to be a CFC. Advances in technology developments and the use of information communication and technology ("ICT") have given rise to what is referred to as the digital economy. The term refers to economic activities hinged on the use of ICT and the internet. Digitalisation has made it possible for a business to carry on economic activity without the need for a multitude of offices, staff, equipment, and other resources. As a result, new business models like Uber and Shien have emerged. This paper argues that the current South African CFC rules have not kept pace with these new business models and do not effectively regulate the new business models and the digital economy. This paper recommends that the CFC rules be updated to address the digital economy and new business models by amending the rules, incorporating the provisions of Electronic Communications and Transactions Act 25 of 2002 into the rules, using country-by-country reporting, and even considering implementing a regime alternative to CFC rules.
Keywords: Anti-avoidance; Controlled foreign company; Deemed source; Digital Economy; Digitalisation; Direct tax; Foreign business establishment exemption

Tacit Choice of Law in International Commercial Contracts. An Analysis of Future Instruments of Developmental Organisations - Bouwers, Garth J. (Potchefstroom Electronic Law Journal, 2023)
This article examines the various regional and supranational organisations of emerging countries that could benefit from a codification of private international law rules. They include the Organisation for the Harmonisation of Business Law in Africa (OHADA), the African Union (AU) and the Association of Southeast Asian Nations (ASEAN). In addition, the article analyses the envisaged instruments that may be especially relevant in the context of the abovementioned organisations. These include the Preliminary Draft Uniform Act on the Law of Obligations in the OHADA Region, the proposed African Principles on the Law Applicable to International Commercial Contracts and the Asian Principles of Private International Law. More specifically, the article focusses on the provisions regarding the determination of the law applicable, particularly those rules relating to a tacit choice of law in international commercial contracts.
Keywords: ASEAN; African Union; Asian Principles of Private International Law; Choice of Law; International Commercial Law; OHADA; Private International Law; Tacit choice of law

The Concise Encyclopedia of Business Ethics - MacDonald, Chris; Marcoux, Alexei (Toronto Metropolitan University, 2023)
The authors’ aim in writing The Concise Encyclopedia of Business Ethics (CEBE) was to provide readers with a useful, concise overview of key issues in business ethics. Our aim is not to be exhaustive, but to provide key definitions, main areas of controversy, and pointers for further reading. It is hoped that it will provide a useful reference guide for students, as well as a starting point for scholars in adjacent fields. Our commitment to sticking to what we consider to be essential topics inevitably means that some readers will find that we have left out what they take to be important topics. For the most part, we stand by our editorial choices. However, as a digital document, it is possible that the CEBE will change and grow slightly over the coming years. Readers are free to provide feedback and suggestions by emailing the authors jointly at editors@bejr.org

Liability in the atmosphere of groups of companies - Motassim, Sofia (Universitat de Barcelona, 2023)
Groups of companies are a complex corporate structure, whose regulation can be problematic, especially when it comes to liability. Indeed, liability within corporate groups draws forth a series of issues principally due to the principles of separate corporate personality and limited liability. In the context of limited liability, which is based on the notion of separate legal personality, the main issue waxes the protection of the creditors, in particular the creditors of the subsidiaries. One can find three regulatory templates for handling corporate groups and their liability: policing via general company and/or civil law (such as the English model); policing via special group legislation (such as the German model); and policing via branches of law such as insolvency law, antitrust law, and contract law, among others (which is the case in numerous jurisdictions, either coupled with the first or the second model). Lifting the corporate veil has come as an answer to corporate separateness, by permitting to ignore the shareholders’ limited liability and hold them personally liable for the debts of their companies in specific circumstances. However, one can hardly find cases in which the corporate veil has been successfully lifted, due to many factors. Other important questions that are posed in the scope of corporate groups liability are the parent company’s liability for the payment of its daughter companies’ debts when insolvency strikes and other respects, besides the matter of group liability. Furthermore, liability is as well a key player in terms of tort law, and corporate social responsibility has therefore found a place in the sun in the present climate.
Alternate link : https://diposit.ub.edu/bitstreams/83cde66e-b943-45b6-830b-831df41cb73f/download
Keywords: Ciències Jurídiques; Commercial law; Conglomerate corporations; Corporations; Derecho mercantil; Dret mercantil; Econòmiques i Socials; Grupos de empresas; Grups d'empreses; Liability (Law); Responsabilidad (Derecho); Responsabilitat (Dret); Sociedades; Societats

The Autonomy Doctrine in the Law of Letters of Credit and Demand Guarantees in Libya, Egypt and England: A Comparative Study - Mukhtar Elhouderi, Tajeldin Eissa Saleh (University of Leicester, 2023)
Letters of credit and demand guarantees play a prominent role in financing international trade. They provide assurance of payment and security for the performance of contractual obligations and have been described as the ‘lifeblood’ of international commerce. Autonomy is the central principle for the instruments of letters of credit and demand guarantees. Under the autonomy principle, the bank’s undertaking to pay for the beneficiary ought to be independent of the diversity of other relationships arising from the underlying contract. In spite of the autonomous nature of these instruments, in certain cases, the national laws will recognise some exceptions or limitations that restrict the application of the doctrine of autonomy. Exceptions such as fraud, nullity, and illegality will allow the national courts to interfere and override the autonomy doctrine by considering other matters, even those concerning the underlying contract. Furthermore, the exceptions of unconscionability or abuse of rights have an effective role in providing deep solutions, especially with regard to the problem of abusive calls for demand guarantees. The autonomy principle is recognised under Libyan commercial law but has yet to form the subject of serious academic literature covering its legal aspects. This study, in part, aims to fill that gap and will examine the extent to which legal aspects govern the principle of autonomy and its exceptions under Libyan law with reference to the new Libyan Commercial Code. A comparison of the laws in England, Libya, and Egypt will be conducted to examine how legal matters concerning autonomy and its restrictions in their laws are addressed. Furthermore, consideration will be given to the experience of Singapore, particularly with regard to the unconscionability and nullity exceptions. The results of this study will consider many different exceptions to autonomy and suggest that fraud is not the only exception to autonomy and that it is not imperative that all exceptions in letters of credit be equally applied to demand guarantees.
Keywords: Commerce international; Comparative study; Contractual obligations; Egypt; England; International Trade; International commerce; Letter of credit; Letter of guarantee; Lettre de crédit; Lettre de garantie; Libya; Obligation contractuelle

Impact of the Commercial Law on E-Commerce Practices and Business Sustainability in Nigeria - Ufua, Daniel Ebakoleaneh; Olujobi, Olusola Joshua; Al-Faryan, Mamdouh Abdulaziz Saleh (International Journal of Management, Economics and Social Sciences, 2023)
With the advent of global market interdependence and interaction, coupled with the consistent spread of the internet facilities across geographical boundaries, businesses engage in e-commerce practices either to augment existing on-ground businesses or as independent outfits. This study focused on the law on e-commerce practice and business sustainability in Nigeria. The study applied a conceptual review focusing on the trends of development of ecommerce practice and the supportive effects of the legal system in facilitating business sustainability in Nigeria. The study relied on extant literature sourced from various outlets, relevant to the topic of this study. The key findings highlighted and discussed factors for improved e-commerce practices in Nigeria. These included access to legal services, effective government policy and institutional support, time and fair interpretation of the law governing e-commerce, continuous evaluation of the ecommerce processes in Nigeria, increased awareness and familiarity with e-commerce facilities, and the adoption of suitable technology. The study provides valuable insight into the support of the Nigerian commercial sector on e-commerce practices. The adoption of systems theory enhances the promotion of fairness across the entire ambience of e-commerce practice and the support of the law. This implied focusing on the continuous evaluation of legal support and a flexible process of developing the needed approaches to address emerging changes in e-commerce that can enhance business sustainability in Nigeria.
eprints.covenantuniversity.edu.ng
Keywords: Business sustainability; E-commerce; Flexible process; Government Policy; Legal system support; Nigerian economy

Overcoming Divergence in English and French Contract Law: A Common Taxonomy of Commercial Contracts - Pedamon, Catherine (University of Westminster, 2022)
The works presented for the PhD by publication are all connected in the way they engage in a functionally comparative study of the English and French law responses to common problems pertaining to contractual performance and contractual interpretation. My comparative inquiry demonstrates that both France and England have stayed true to their historic responses in times of peace and crisis confirming different mentalités juridiques. As neither England nor France offers ideal solution, parties may be better off finding a resolution to their disputes beyond the legal realm and respond to calls for collaboration. This nevertheless shows persisting differences in Anglo-French approaches. This thesis however argues that these divergences may nevertheless lead to common results through the lens of a taxonomy of commercial contracts – professionally drafted contracts may lead to converging results given the common application and interpretation of frequently used clauses beyond a domestic legal culture; by contrast, rudimentary contracts produce diverging results as the interpretation of these agreements is marked by a distinctive domestic socio-legal culture. This taxonomy has the potential to improve the predictability of outcomes in commercial disputes in England and France.
Keywords: Commercial contracts; Contract law; England; France

International Commercial Law Emerging in Africa - Neels, Jan L. (Potchefstroom Electronic Law Journal, 2022)
This article provides an overview of the history of international commercial law in Africa with reference to instruments of the three sister organisations of private international law (in a wide sense): UNCITRAL (the United Nations Commission on International Trade Law), UNIDROIT (the International Institute for the Unification of Private Law) and the HCCH (the Hague Conference on Private International Law). The adoption of UNIDROIT's Cape Town Convention on International Interests in Mobile Equipment of 2001 is identified as a possible watershed moment in respect of the future development of international commercial law in Africa. Following the creation of an African Continental Free Trade Area by member countries of the African Union, it is suggested that participating states reconsider joining the United Nations Convention on the International Sale of Goods (1980) (CISG) and incorporating the UNCITRAL Model Law on International Commercial Arbitration (1985/2006), which are in a certain sense the two founding documents of the modern lex mercatoria. Another priority, the author suggests, is that Africa needs a supporting instrument on the private international law of contract. The first draft of the African Principles on the Law Applicable to International Commercial Contracts is then discussed with an emphasis on the role of substantive law instruments, in particular the CISG
Keywords: African Principles of Commercial Private International Law; African Principles on the Law Applicable to International Commercial Contracts; International Commercial Law; International commercial contracts; Private international law

Article 255 of the OHADA Uniform Act on General Commercial Law and Consumer Protection: The Need to Experiment - Djieufack, Roland (International Journal on Consumer Law and Practice, 2022)

Influence of current and capital account liberalization on economic growth: Evidence from heavily indebted SSA economies - Leykun, Fentaw (African Journal of Economic and Business Research, 2022)
Capital and current account restrictions were widely used in the past but were largely released during the liberalization movement of the 1990s, as interventionist policies got widespread support that paves the way to the renewed conception of government as an impartial referee. Such a restriction has come back on the agenda with the surge in public debt in the rouse of the Global Financial Crisis. By distorting market signals and incentives, financial repression persuades losses from inefficiency and rent-seeking that cannot be easily quantified. This paper seeks to investigate the impact of current and capital account liberalization on growth, using recent de jure and de facto measures, covering 26 heavily indebted Sub-Saharan African countries over 2000-2020. The results suggest that capital account liberalization escalates growth, brought distributional efficiency in conformity with the neoclassical growth model.
Keywords: Capital account; Current account; Economic growth; Financial liberalization; Financial repression

Exporting the Luxembourg Rail Protocol to the Convention on International Interests in Mobile Equipment to Africa - Otabor-Olubor, Iyare (Uniform Law Review, 2022)
This article recommends the Cape Town Convention on International Interests in Mobile Equipment and appeals to African countries to accede to the Luxembourg Protocol on Railway Rolling Stock (Rail Protocol). The discussion in this article focuses on the extent to which Article XXII of the Rail Protocol can be applied with respect to Africa. The article critically analyses the competence of the African Economic Community (AEC) and its sub-regional organizations to accede to the Cape Town Convention and Rail Protocol. The author provides a detailed argumentative analysis of the legal mandate of the AEC and the influence of African Union (AU) laws on the competence of the AEC’s sub-regional organizations to make declarations under the Cape Town Convention and Rail Protocol. The analysis confirms that competence to accede to the Convention and Rail Protocol resides with sovereign States in Africa and not with the AU, the AEC, the Organisation pour l’harmonisation en Afrique du Droit des Affaires, or any existing sub-regional organization in Africa.

Factors affecting the probability of formalizing informal sector activities in Sub Saharan Africa: evidence from World Bank enterprise surveys - Moyo, Busani (African Journal of Economic and Management Studies, 2022)
Purpose This study aims to investigate the factors that affect the likelihood of formalizing informal sector activities in 13 Sub-Saharan African countries, using World Bank enterprise survey data collected between the periods 2009 and 2018. Notwithstanding the great contribution of the informal economy in Africa, developing countries may stand to gain more if they make inroads in formalizing the informal sector. Design/methodology/approach Since the dependent variable is binary taking the value of one if the firm is willing to formalize and zero otherwise, the study will employ a discrete choice probit model. Findings Results inter alia show that firms that are more likely to formalize are young, owned by individuals with high levels of education and, have registered before. Governments should therefore target firms that are young and provide them with information about the benefits of registration, and if these firms are owned by experienced and educated individuals, the likelihood for them to register would be high. Research limitations/implications The study uses cross sectional data and therefore cannot capture time variant factors affecting the probability to register and also cannot correct effectively for endogeneity. Practical implications Governments should therefore target firms that are young and provide them with as much information as possible about the benefits of registration, and if these firms are owned by experienced and educated individuals, the likelihood to convince them to register would be high. They should also reduce the cost of registration so as to improve net benefits in line with the rational exit view. Social implications Formalizing informal activities will help improve the performance of these firms, reduce vulnerable employment as well as crime, poverty and inequality. Providing decent operating and working conditions to informal players will reduce social and political unrest. Originality/value The African continent is home to many informal firms accounting for roughly 55% of economic activity with 90% of workers eking out a living in a sector that does not respect worker rights, provide decent working conditions and where changes in growth have done little to reduce its size. Regulatory reforms have also been implemented resulting in the number of start-up registration procedures falling from 11 in 2003 to seven in 2019. The uniqueness of Sub Saharan Africa in terms of entrepreneurial culture, political, institutional and economic conditions as well as lack of consensus in the extant empirical literature make this study pertinent.
Keywords: Formalization; Informal; World Bank and Africa

The Limits of Public Contract Law - Casey, Anthony J.; Niblett, Anthony (Law and Contemporary Problems, 2022)
This work received SSHRC funding
Accepted: 2023-06-19T20:16:27Z

The conclusion of contracts by electronic agents in the age of the Fourth Industrial Revolution : a South African perspective - Doughan, Albert Nana (University of Johannesburg, 2022)
Please refer to full text to view abstract.
Keywords: Commercial law; Contracts; Electronic data interchange; Industry 4.0

The Processes of Democratization and Economic Development in Africa: A Case Study of the Democratic Republic of Congo (DRC) Since 2006 - Otshudi Talo, Esperance (Near East University, 2022)

The Impact of Covid-19 Pandemic on Women In Nigeria - Iheanacho-Shahid, Jennifer (African Journal of Politics and Administrative Studies, 2021)
The paper examines the impact of corona-virus pandemic on women in Nigeria. Emergencies and times of unrest have been linked with increasing reports of Gender Based Violence. Pandemics and Epidemics on the other hand are no exception. The COVID-19 pandemic has been associated with an increase in Gender Based Violence termed the Shadow Pandemic due to the control measures adopted in containing the spread of the virus. The paper adopted the Social Ecological Model to explain and understand the factors that contribute to the increase of Gender Based Violence against women during emergencies or natural disasters and how interaction of individual and environmental factors influence behavior and attitudes that create an atmosphere that encourages violence. The paper was based on secondary sources of data.  The findings of the paper revealed that the lockdown isolated women and attenuated opportunities for them to divulge the abuse or receive necessary support services or resources.  The paper also discovered that there has been an increased rate of reported cases of Gender Based Violence during the months of lockdown in Nigeria. The paper concluded that the corona-virus outbreak has exposed the shadow pandemic of violence and inequality and the exclusion of the Minister of Women Affairs and Social Development is a step in the wrong direction . The paper recommended that it is pertinent to integrate gender lens into disease response and protection mechanism and Gender Based Violence services should be termed as essential duties during crisis and emergencies.

Challenges and solutions for the harmonisation of contract law within the BRICS countries. Invalidity of contracts and hardship - Veronese, Lígia Espolaor (Universidade de São Paulo, 2021)
The present thesis is concerned with a comparative study of contract law applicable in the BRICS countries Brazil, Russia, India, China and South Africa with a strong focus on the issues of invalidity of contracts and hardship. The purpose is to identify commonalities and divergences in these systems with different legal backgrounds, particularly the influence of civil law tradition in Brazil, Russia and China as opposed to common law in India, and the mixed system in South Africa. Among the identified divergences and challenges, the thesis purports to demonstrate that the obstacles are not insuperable and that there are rooms for the harmonisation and compatibility within the BRICS context with respect to the two selected topics of contract law. Even when full harmony is not reached, the research also purports to demonstrate that some countries may benefit from others divergent experiences. Detecting mutual contribution is of particular relevance to this group of countries, since they share the characteristic of being evolving systems which have undergone recent reforms in their legislation on contract law and may be more open to assess and incorporate more efficient contract practices.
Keywords: BRICS; Brazil; Common law vs. Civil law; Comparative law; Contract law; Contribuição; Contribution; Direito comparado; Direito contratual; Hardship; Harmonisation; Harmonização; Invalidade dos contratos; Invalidity of contracts; Russia; South Africa; Validade dos contratos; Validity of contracts

Big Data and Global Trade Law - Burri, Mira (Cambridge University Press, 2021)
This collection explores the relevance of global trade law for data, big data and cross-border data flows. Contributing authors from different disciplines including law, economics and political science analyze developments at the World Trade Organization and in preferential trade venues by asking what future-oriented models for data governance are available and viable in the area of trade law and policy. The collection paints the broad picture of the interaction between digital technologies and trade regulation as well as provides in-depth analyses of critical to the data-driven economy issues, such as privacy and AI, and different countries' perspectives. This title is also available as Open Access on Cambridge Core.
Keywords: AI; Artificial Intelligence; Big data; Blockchains (Databases); Data protection––Law and legislation; Foreign trade regulation; Inteligência artificial; Intelligence Artificielle; Law and legislation; Transborder data flow––Law and legislation.; World Trade Organization

The Impact of Economic Institutions on Small Firms in Developing Countries - Pouliquen, Victor (Ecole des Hautes Etudes en Sciences Sociales, 2019)
In many developing countries, economic institutions are failing. This translates into structural problems such as widespread informality, rampant corruption and the impossibility for governments to raise taxes. This thesis study how economic policies affect economic institutions in developing countries. It focuses on two broad questions: (1) What are the effects of policies to reduce informality? and (2) how are new technologies reshaping the way governments collect taxes?The first chapter uses a randomized experiment to study the introduction of a new legal status in Benin, created to make it easier for small firms to become formal. To make this new status attractive, the government added supplementary incentives designed to enhance the presumed benefits of formalizing. We find that few firms register when just given information about the new regime, but our full package of supplementary efforts boosts formalization by 16.3 percentage points. However, this formalization does not bring firms higher sales, profits or access to credit, and the cost of formalizing these firms exceeds the added taxation they will pay over the next decade. We show how better targeting of these policies towards firms that look more like formal firms to begin with can increase the formalization rate and improve cost-effectiveness. The second chapter studies the impact of formalization on intra-household relationships, still in Benin. The idea behind this chapter is that formalization changes effective property rights by clarifying who in the household is the legal owner of the business and who will keep it in case of divorce. The causal effect of formalization is identified using the same random experiment used for the first chapter. We find first that formalization increases entrepreneurs' (both male and female) control over household revenue. They contribute proportionally less to household expenditures and to the personal expenses of their partner. Second, using a behavioral game, we find strong gender differential effects of formalization on the probability that entrepreneurs pay to hide a windfall transfer from their spouse. Female entrepreneurs are much more likely to pay to hide, while male entrepreneurs are much less likely to do so. Using a theoretical model, we show that this result is compatible with the idea that women entrepreneurs are constrained and cannot invest as much as they would like in their own business. Women who became formal hide the windfall transfer more because they have more property rights and want to invest more in their business. Our conclusion is that formalization has important effects on intra-household dynamics.The third and final chapter of this thesis deals with the second question and examines how internet is changing the way taxes are collected. Specifically, we study the impact of electronic tax filing (e-filing) for small firms to replace in-person submission of paper-based forms to tax officials. We examine the impact of e-filing on compliance costs, tax payments, and bribes payments using experimental variation and data from Tajikistan firms. We find that firms that e-file have lower compliance costs, spending five fewer hours each month on fulfilling tax obligations. There are no significant average effects of e-filing on tax or bribe payments, but significant heterogeneity exists across firms by their baseline likelihood of tax evasion. Among firms previously more likely to evade, e-filing doubles tax payments, likely by disrupting collusion with officials. Conversely, among firms less likely to have been evading, e-filing reduces tax payments, suggesting that officials had previously required them to pay more. These firms also pay fewer bribes, as e-filing reduces opportunity for extortion. Our conclusion is that e-filing reduces compliance costs and makes the distribution of tax payments across firms arguably more equitable. Dans les pays en développement, les institutions économiques sont souvent défaillantes. Cela se traduit par des problèmes structurels tels que l’omniprésence du secteur informel, la corruption généralisée et l’incapacité des États à collecter les impôts. Cette thèse porte sur les politiques publiques permettant d’améliorer le fonctionnement des institutions économiques. Elle se focalise sur deux questions : (1) Quels sont les effets des politiques de réduction de l’informalité ? et (2) Comment les nouvelles technologies affectent la collecte des taxes ? Le premier chapitre étudie à l’aide d’une expérimentation aléatoire l’introduction d’un statut légal facilitant la formalisation des petites entreprises au Bénin. Afin de rendre ce statut attractif le gouvernement l’a accompagné d’incitations supplémentaires créés pour amplifier les bénéfices potentiels de la formalisation. Nous trouvons que très peu d’entreprises se formalisent lorsqu’elles reçoivent uniquement de l’information sur le nouveau statut. Cependant, lorsque l’information est combinée aux incitations, la formalisation augmente de 16,3 points de pourcentage. En revanche, les effets sur les performances des entreprises sont limités, et le coût des incitations est supérieur au total des impôts qu’elles paieront pendant les 10 prochaines années. Enfin, nous montrons comment un ciblage sur les entreprises ayant des caractéristiques proches des entreprises déjà formelles améliorerait l’efficacité de ce type de programme. Le second chapitre étudie l’impact de la formalisation sur les relations intra-ménages, toujours au Bénin. Dans ce contexte, la formalisation renforce les droits de propriété et clarifie au sein des ménages qui est le propriétaire légal de l’entreprise, et qui la gardera en cas de divorce. L’effet causal de la formalisation est identifié à l’aide de l’expérimentation aléatoire déjà utilisée pour le premier chapitre. Nous trouvons que les entrepreneurs s’étant formalisés ont plus de contrôle les ressources de leur ménage. Ils ou elles contribuent proportionnellement moins aux dépenses du ménage et transfèrent moins d’argent à leur partenaire. Deuxièmement, en utilisant un jeu comportemental dans lequel les entrepreneurs peuvent cacher un transfert monétaire à leur partenaire, nous trouvons que les femmes qui se sont formalisées cachent davantage à leur mari. A l’aide d’un modèle théorique, nous montrons que ce résultat est compatible avec l’idée que les femmes ne sont pas libres d’investir comme elles le souhaiteraient dans leur entreprise et doivent le faire secrètement. Notre conclusion est que la formalisation a des effets importants sur les dynamiques intra-ménage. Le troisième chapitre utilise une expérimentation aléatoire conduite au Tadjikistan pour étudier l’impact d’un système permettant aux entreprises de déclarer leurs taxes en ligne plutôt que de soumettre un formulaire en personne. Nous trouvons que ce système réduit le temps passé par les entreprises pour remplir leurs obligations fiscales de 5 heures par mois. Nous ne trouvons pas d’effets sur le montant des impôts payés ni sur le versement de pots-de-vin. En revanche, l’absence d’effets moyens masque une importante hétérogénéité. Les entreprises le plus susceptibles de faire de l’évasion fiscale dans le système précédent payent davantage d’impôts quand elles déclarent en ligne, probablement car elles ne peuvent plus entrer en collusion avec les agents des impôts. À l'inverse, les entreprises qui étaient les moins susceptibles de faire de l’évasion, payent moins des taxes quand elles déclarent en ligne, suggérant qu’elles étaient forcées de payer plus d’impôts avant. Ces entreprises paient également moins de pots-de-vin, ce qui suggère que déclarer en ligne offre une protection contre le risque d'extorsion de la part des agents du fisc. Notre conclusion est que permettre la déclaration des taxes en ligne a rendu l’appareil fiscal à la fois plus efficace et plus juste.
Keywords: Droits de Propriétés; Electronic Tax Filing; Impôt; Impôt (recouvrement); Informality; Informalité; Innovation; Intra-Household Relationships; New Technologies; Nouvelles Technologies; Paiement en ligne des Taxes; Petites Entreprises; Petites et moyennes entreprises; Property Rights; Propriété; Relations Intra-Ménage; Small Firms; Taxation; Économie souterraine

Multidimensionality of Sustainable Public Procurement (SPP) - exploring concepts and effects in Sub-Saharan Africa and Europe - Stoffel, Tim; Cravero, Carol; La Chimia, Annamaria; Quinot, Geo (Sustainability, 2019)
Strategic objectives in public procurement, such as environmental or social considerations, are being increasingly referred to under the umbrella term of sustainable public procurement (SPP). The concept of sustainability is intrinsically multidimensional, encompassing environmental, social, and economic aspects. However, the existing literature on SPP highlights the generalization that the regulation and practices of public procurement are biased toward the environmental dimension. There is conflicting evidence from countries in Sub-Saharan Africa (SSA) that calls for further investigation. Analyzing how SPP is actually constituted in SSA and contrasting it with the situation in the European Union (EU), as a spotlight on the Global South and North, contributes to a better understanding of sustainability in public procurement. The comparative analysis will help with understanding processes related to the integration or disintegration of sustainability dimensions in SPP. Our results indicate a contrary orientation on the environmental and the social dimensions in the EU and SSA. Although there is no sign of a comprehensive integration of all dimensions in SPP, there are developments toward the integration of the ‘missing’ dimension in the respective regional setting. Thus, at the moment, achieving a multidimensional implementation of SPP appears to be more a matter of expanding SPP practices of the ‘missing’ dimension than of pushing for integrated concepts.
http://hdl.handle.net/10019.1/124395
Keywords: GPP; Government purchasing; Green public procurement; Multidimensional sustainability; SRPP; Socially responsible public procurement; Socioecological transformation; Sustainable development; Sustainable supply chains

Rationality and legality of non-market economy treatment in Antidumping law: novel perspectives on the changed legal environment - Long, Shao (Universität Wien, 2019)
AD Recht ermöglicht die Anwendung des Instruments nichtmarktwirtschaftlicher Behandlung (NME) zwecks Bestimmung des normalen Ausfuhrpreises von importierten Waren aus Ländern deren Märkte als weitgehen von Regierungen beeinflusst und deren Preise und Kosten für diese Berechnung als unverlässlich angesehen werden. Stattdessen sollten diese Berechnungen auf der Basis von Preisen in einem Vergleichsland mit funktionierender Marktwirtschaft ( „surrogate country‟ ) erfolgen. Die vorliegende Dissertation legt dar, dass die Anwendung der NME Behandlung zum Schutz gegen unfairen Importwettbewerb nicht auf rechtlich gesicherter Grundlage erfolgt, sondern als willkürlich eingeseztes protektionistisches Instrument gehandhabt wird. Besonders die Anwendung dieser Methode auf Chinesische Exporte nach 2016 ist rechtlich fragwürdig. Die Dissertation untersucht die Rechtmäßigkeit und Zweckmäßigkeit diese Methode, erstens durch die Analyse der wirtschaftlichen Begründung des AD Rechts und der geschichtlichen Entwicklung seit seinen protektionistisch motivierten Anfängen. Sie untersucht sowohl die relevanten Regeln und Praktiken aus der Zeit vor der Gründung der WTO als auch solche die danach zur Anwendung kamen und kommt zum Schluss, dass sie angesichts des grundlegend geänderten globalen rechtlichen Umfelds nicht mehr tragbar sind. Die Autorin empfiehlt daher, dass die auf NME Behandlung bezogenen Regeln und Praktiken vollständig aufgegeben werden und im Rahmen der gegenwärtigen Bemühungen um eine Modernisierung des gesamten WTO Regelwerks durch angemessene andere Regeln ersetzt werden sollten.
https://phaidra.univie.ac.at/detail/o:1354372
Keywords: Antidumpingrecht; Nichtmarktwirtschaftlichen Behandlung; Non-market economy

Sustainable tourism development in transfrontier conservation areas : a legal perspective - Mugadza, Amanda Tapiwa (North-West University, 2019)
Transfrontier conservation areas (TFCAs) originate from the idea of conservation across international boundaries. Within the SADC region, they are defined as areas or components of large ecological regions that straddle the boundaries of two or more countries, encompassing one or more protected areas, as well as multiple resource use areas. While the objectives of TFCAs are manifold, key among these are biodiversity conservation, improvement of livelihoods - poverty alleviation and economic development. Within SADC, tourism is identified as a key driver of these objectives. To explore this further, the study embarks on a case study of the Great Limpopo Transfrontier Conservation Area (GLTFCA), the oldest and second largest TFCA in the region, involving South Africa, Mozambique and Zimbabwe. From the GLTFCA, it is established that challenges exist with the manner in which tourism development is undertaken. However, it is further established that these challenges do not necessarily stem from the tourism development itself but from the weaknesses in the governance structures of this TFCA. In particular, the exclusion of local communities as key governance actors in the GLTFCA is seen to be detrimental to conservation and perpetuates poverty. Superimposed on these weaknesses, the tourism development therefore fails to adequately promote biodiversity conservation, improvement of livelihoods - poverty alleviation and economic development in the GLTFCA. To resolve these challenges, the study explores the concept of sustainable tourism development from a legal perspective guided by the question: what is the legal framework necessary, at domestic level – in TFCA participating countries to ensure that sustainable tourism development promotes the key SADC TFCA objectives? Through the aims or policy implications of sustainable tourism development, the study determines a legal framework comprising of the relevant TFCA governance actors as well as the governance-based tools that are necessary to promote the TFCA objectives. The domestic legal frameworks of the GLTFCA participating countries are measured against this legal framework to establish whether they promote sustainable toruism development. It is established that the domestic legal frameworks of South Africa, Mozambique and Zimbabwe, individually and as a whole, neither provide effectively for all relevant TFCA governance actors, especially local communities; nor for the tools that promote biodiversity conservation, the improvement of livelihoods-alleviation of poverty and economic development in the GLTFCA. Thus, the legal framework of the GLTFCA does not provide for sustainable tourism development as it should. For this reason, the study’s principal recommendation is the adoption, by all SADC TFCA participating countries, of a domestic legal framework for sustainable tourism development with specific elements which provides for the key TFCA governance actors as well as the relevant governance-based tools.
Keywords: Biodiversity conservation; Domestic legal framework; Economic Development; GLTFCA; Governance actors; Governance-based tools; Improvement of livelihoods; Sustainable tourism development; TFCAs; Tourism

An Empirical Study of Dispute Resolution Clauses in International Supply Contracts - Coyle, John F.; Drahozal, Christopher R. (Vanderbilt Journal of Transnational Law, 2018)
International transactions present unique legal risks. When a contract touches several different nations, a party may not know where it will be called upon to defend a lawsuit or, alternatively, which nation’s law will be applied to resolve that dispute. To mitigate these risks, parties will often write dispute resolution provisions into their contracts. Arbitration clauses and forum selection clauses help to reduce uncertainty relating to the forum. Choice-of-law clauses help to reduce uncertainty as to the governing law. Over the past few decades, such provisions have become commonplace in international contracting. And yet there exist vanishingly few empirical studies exploring the use of these provisions in international commercial agreements.

The position of assets vested in a sham trust - Diedericks, C. A. (North-West University, 2018)
The concept of a sham trust has changed over the years. Presently it is defined as a perceived entity that is not entirely what it portrays to be. In addition, a sham is therefore regarded as invalid with a deceiving nature. A sham trust has the consequence that all the benefits and protection of assets are destroyed, seeing that no trust actually came into existence. Considering the above, for the purpose of the present study, only an inter vivos trust was evaluated and discussed in detail. The law of contract is considered to be the foundation of the principles for an inter vivos trust. Therefore, the law of contracts can be applied to solve problems presented by trusts. During the course of the present research, it became evident: in instances where a trust is declared a sham, the consequence is that the trust will be deemed void. There are instances where a sale agreement has been concluded prior to the discovery of the true nature of the trust, namely it being a sham. This raises the question on the legal position of assets vested in a sham trust. A further question arises about the consequences and whether the courts should set a guideline for such instances. From the findings it is evident that such a guideline is necessary. This would enable courts to determine the consequences of assets vested in a sham trust. There are various possibilities regarding consequences for assets vested in a sham trust. To determine the applicable consequence, the court should deal with each case individually based on the facts of that particular circumstances. This consequence could either entail that the assets should fall within the founder’s personal estate, or whether the concluded sale agreement should be deemed void. It is evident that the courts struggled with the distinction between a sham and alter ego trust, however, the case law referred to below gives more clarity in this regard. A proper formulation of the aspects of sham and alter ego trusts was provided in the cases of Van Zyl v Kaye1 and Van der Merwe v Hydraulics.2 The formulation of the two aspects in the above-mentioned cases was confirmed in the Supreme Court of Appeal judgement in the case of WT v KT.3 In the Khabola v Ralitabo,4 the court dealt with the typical example of the sham trust. In brief, the fact of the case were, that the parties had the intention to establish a partnership that was simulated to be a trust.
Boloka Institutional Repository https://repository.nwu.ac.za/handle/10394/31321
Keywords: Assets; Contract of sale; Intention; Law of contract; Legal position; Sham trust; Snook test; inter vivos trust

The Organisation for the Harmonisation of Business Law in Africa (OHADA) System: Overview of some Benefits and Problem Areas - Leno, Ngaundje Doris (International Journal of Advanced Research and Publications, 2018)
As much as the Organisation for the Harmonisation of Business Law in Africa (OHADA) aims to improve the legal environment for business, the harmonisation process should be seen as a tool of economic integration with several advantages. Despite the achievements and benefits, OHADA, like other regional integration efforts in Africa, has some temporary drawbacks that may become permanent if no effort is made to overcome them. The primary focus of the paper is to present OHADA‟s background; offer an overview of some of the salient benefits of OHADA‟s institutional and regulatory framework; consider OHADA‟s problem areas; and propose possible solutions to the problems. The value of the paper, therefore, lies in the insight it offers into OHADA, the benefits and problems of its institutional and regulatory framework. It is also important because it is laying the foundation in making the OHADA structure available for all Africans.
Keywords: Business law; Harmonisation; OHADA

Modifying contract law principles to accommodate automated transactions in South Africa - Ramokanate, L. L. (North-West University, 2018)
Modern electronic commerce is chiefly characterised by the use of unattended computers in the negotiation and conclusion of agreements. Commonly referred to as "electronic agents," these computers assist their users to negotiate better and profitable deals in virtual marketplaces. In South Africa, the legal force and effect of automated transactions, i.e. agreements concluded by electronic agents, is addressed in section 20 of the Electronic Communications and Transactions Act 25 of 2002 (hereinafter referred to as the ECT Act). According to section 20 (a) of the ECT Act, a valid and enforceable agreement will be formed where an electronic agent performs an action required by law for agreement formation. The same statute provides further in section 20 (b) that a valid and enforceable agreement will be formed where all the parties to a transaction or either one of them uses an electronic agent. The overall effect of these provisions is that an agreement cannot be denied legal validity and enforceability on the ground that an electronic agent was used, whether by one or both parties, to conclude it. Likewise, an agreement cannot be denied legal validity and enforceability on the ground that no human being took part in its formation. Although the ECT Act provides as a general matter that automated transactions are valid and enforceable in South Africa, that statute does not, however, create new rules for the formation of such agreements. This is made clear in section 3, which provides, amongst others, that the ECT Act should not be interpreted to exclude the application of the common law of contract to electronic transactions. Therefore, as with traditional or non-automated agreements, automated transactions too must satisfy the individual requirements of a valid contract at common law. As a matter of fact, the common law theory of contract formation is predominantly based on the assumption that human volition will always play a pivotal role in the making, acceptance or rejection of offers. For that reason, this research proceeds on a strong hypothesis that common law rules and principles pertaining to the formation of agreements are either insufficient or inadequate to accommodate the validity of agreements concluded by computers without the immediate intervention of their users. Consequently, the aim of this research is to discuss how the rules and principles of the common law of contract can be modified or developed in order to accommodate, within the common law theory of contract formation, the statutory validity of automated transactions in South Africa. The discussion of this research is limited to five legal issues, namely the basis of contractual liability in automated transactions, the analysis of offer and acceptance in automated transactions, the time and place of contract formation in automated transactions, the incorporation of standard terms and conditions in automated transactions, and the treatment of mistakes and errors in automated transactions. These issues are discussed first with reference to South African law, primarily with the purpose of determining the extent to which relevant common law rules and principles provide adequate solutions to specific challenges posed by automated transactions. To the extent that relevant common law rules and principles do not provide adequate solutions to the challenges of automated transactions, recommendations are made in this research for their development or modification. As shall be demonstrated in the course of this work, in relation to some of the abovementioned legal issues, the development or modification of common law rules has been done by the ECT Act. These "statutory developments or modifications of the common law" are also discussed in this work, primarily with the aim of determining the extent to which they provide adequate solutions to specific challenges posed by automated transactions. To the extent that these statutory modifications of the common law do not provide adequate solutions to the challenges of automated transactions, recommendations are made in this work on how the relevant provisions of the ECT Act may be interpreted by courts of law or amended by Parliament in order to strengthen the response of that statute. The abovementioned legal issues are also discussed in this work with reference to US and UK law, primarily with the purpose of determining how the law addresses the challenges of automated transactions in these jurisdictions, and to draw valuable lessons for the development or modification of South African contract law.
Keywords: Automated transactions; Autonomous electronic agents; Contract formation; Contract law; Passive electronic agents

What Do Trade Agreements Really Do? - Rodrik, Dani (The Journal of Economic Perspectives, 2018)

The impact of climate change law on the principle of state sovereignty over natural resources - Van Wyk, Sanita (Stellenbosch University, 2017)
This dissertation serves to expand the means within international law by which to address the global interdisciplinary crisis that is climate change. The principle of sovereignty over natural resources is identified as a principle of international law, evolutionary in nature, fundamentally connected to the international legal climate change regime, and able to be impacted by the effects of climate change. The gravity of climate change is illustrated, as is the intricacy and composition of the international legal climate change regime. In the process, a particular shortcoming of the international legal climate change regime is identified, namely the lack of state compliance with climate commitments made in terms of the Kyoto Protocol 1997 and the Paris Agreement 2015. The gravity of the effects of climate change warrants the repositioning of any principle of international law that is able to address this shortcoming of the international legal climate change regime and increase the effectiveness of the regime. In this regard it is determined, more specifically, that the gravity of the effects of climate change warrants a reinterpretation and reconfiguration of the principle of sovereignty over natural resources. Climate change, forming part of the general, growing, global concern for environmental conservation and sustainable development, influences the interpretation and configuration of state rights and state duties in terms of the principle by eliciting an interpretation that restricts state rights and expands state duties. Furthermore, the gravity of the effects of climate change on the well-being of people, warrants a reinterpretation and reconfiguration of the principle of sovereignty over natural resources as a people-oriented principle as opposed to the conventional state-oriented principle, and ought to be applied with due regard to the rights of people in terms of the principle. The right of people in terms of the principle of sovereignty over natural resources, is identified as the right to economic selfdetermination, which gives effect to the right of people to dispose freely of natural resources. Should this right be promoted in future applications of the principle of sovereignty over natural resources, the right may well be established as constituting a significant basis on which people are able to hold states accountable for climate commitments made in terms of the Kyoto Protocol 1997 and the Paris Agreement 2015. In this way, the principle of sovereignty over natural resources, specifically the implementation of the right of people to dispose freely of natural resources in terms of the principle, presents a negative incentive for state compliance with climate commitments and can contribute to addressing the lack of state compliance within the international legal climate change regime. In summary, this dissertation proposes that the grave effects of climate change warrant a repositioning of the principle of sovereignty over natural resources that allows it to constitute a contribution to climate change law and the global fight against climate change.
URI: http://hdl.handle.net/10019.1/101171
Keywords: Climatic changes; Convention on Climate Change 1997; Convention on Climate Change 2015; Environmental law; Kyoto Protocol; Natural resources; Paris Agreement 2015; Self-determination; Sovereignty; United Nations Framework

Oiling the machine: overriding mandatory provisions and public policy in the Hague Principles on Choice of Law in International Commercial Contracts - Dickinson, Andrew (Uniform Law Review, 2017)
Art. 11 of the Principles on Choice of Law in International Commercial Contracts, adopted by the Council of the Hague Conference in March 2015 contains provisions governing the relationship between the system of law1 chosen by the parties under Art. 2(1) (the “chosen law”) and the laws and policies of other systems. It provides as follows: 1. These Principles shall not prevent a court from applying overriding mandatory provisions of the law of the forum which apply irrespective of the law chosen by the parties. 2. The law of the forum determines when a court may or must apply or take into account overriding mandatory provisions of another law. 3. A court may exclude application of a provision of the law chosen by the parties only if and to the extent that the result of such application would be manifestly incompatible with fundamental notions of public policy (ordre public) of the forum. 4. The law of the forum determines when a court may or must apply or take into account the public policy (ordre public) of a State the law of which would be applicable in the absence of a choice of law. 5. These Principles shall not prevent an arbitral tribunal from applying or taking into account public policy (ordre public), or from applying or taking into account overriding mandatory provisions of a law other than the law chosen by the parties, if the arbitral tribunal is required or entitled to do so. In brief summary, therefore, the first and third paragraphs address the relationship between the chosen law and certain laws and policies of the forum, the second paragraph addresses the relationship between the chosen law and certain laws of legal systems other than the forum, the fourth paragraph addresses the relationship between the chosen law and the certain policies of the legal system whose laws would have applied but for the parties’ choice under Art. 2(1) and the fifth paragraph addresses the limits of the application of the chosen law in arbitration proceedings.

The United Nations Convention on the Use of Electronic Communications in International Contracts at Ten: Practical Relevance and Lessons Learned - Castellani, Luca G. (Journal of Law, Society and Development, 2016)
The United Nations Commission on International Trade Law prepared the first global treaty specifically devoted to electronic commerce law, the United Nations Convention on the Use of Electronic Communications in International Contracts. That treaty builds on the highly successful UNCITRAL Model Law on Electronic Commerce and the UNCITRAL Model Law on Electronic Signatures. This article describes the main goals of the Electronic Communications Convention and its scope of application. In particular, it illustrates how that Convention may fully enable the use of electronic means under other widely adopted treaties such as the Convention on the Recognition and Enforcement of Foreign Arbitral Awards and the United Nations Convention on Contracts for the International Sale of Goods. The article also describes the main substantive provisions of the Electronic Communications Convention, in particular clarifying how that Convention updates and completes the provisions of the UNCITRAL Model Law on Electronic Commerce. This Model Law is the backbone of electronic commerce law in numerous countries and a de facto legislative standard insouthern Africa. Finally, the article describes the manner (or patterns) in which the adoption of the Electronic Communications Convention takes place. It stresses that, while the Convention is often used as a source of inspiration for domestic law reform, in order for it to achieve all its intended goals, its formal adoption as a treaty is necessary. The final message is therefore a call upon all states to consider the adoption of that Convention in order to support the broader use of electronic means, especially in the light of the implications for economic development and the promotion of paperless trade.
Keywords: Convention adoption patterns; Digital signatures; Electronic communications; Electronic contracting; Legal harmonisation

Regional Harmonisation of Contract Law - Is It Feasible? - Zeller, Bruno (Journal of Law, Society and Development, 2016)
This article investigates whether regional harmonisation is merely an academic exercise or a serious attempt to create a uniform contract law in a defined region. It builds on the recently conducted Symposium at Villanova University in 2013 and addresses comparatively the efforts by well-defined regions, namely OHADA, the EU and ASEAN. OHADA has introduced regional uniform laws; the EU is still working on formulating them. Furthermore, UNCITRAL has considered a proposal by the Swiss government to work urgently on a new initiative to further harmonise contract law. Against this backdrop, this article argues that regional proposals to harmonise contract law are akin to saying that ‘ein Gespenst geht um’ (a ghost is going around) (Reich 2006: 425). This is justified, because a proposal to create a harmonised contract law in East Asia has currently also been discussed, but the discussions have stalled. Is there a solution or do we simply admit that regional harmonisation is not possible? The starting point is the CISG, as has been adopted by 80 countries and needs to be considered by any region as a possible, albeit not perfect, solution. If the CISG has already been ratified, the issue, then, is how any regional developments can coexist with it. Or does a ratification of the CISG preclude any regional harmonisation? Secondly, the question must be asked whether regional harmonisation will reduce transaction costs, which is beyond what the CISG was able to achieve. This article argues that as far as the drafting of international instruments isconcerned, a shift in thinking has occurred. Instruments such as the Cape Town Convention are considered to be reforming the law in a particular narrow area rather than attempting to draft codes. Furthermore, the process is driven by industry groups. Regional harmonisation must take note of the ongoing shift and a more fruitful approach is to develop uniform laws through a better understanding and coordination of existing instruments.
Keywords: CISG; Contract law; Regional harmonisation; Uniform law

Dealing with trade defence instruments in the context of economic integration in Africa - El Taweel, Khaled (University of Pretoria, 2016)
The launching of the T-FTA in June 2015 presents an opportunity for accelerating regional integration in Africa towards the establishment of a single market through deepening COMESA-EAC-SADC integration. This milestone can contribute positively to African development. Nevertheless, it faces different structural and technical challenges, including the risk of aggressive export strategies and unfair trade practices, which may wipe away a substantial part of the integration gains. This could undermine African integration plans and the largely infant industries in Africa, especially since many African countries lack sufficient technical skills, institutional capacity, and the legal framework to deal efficiently and effectively with unfair trade practices and to respond to situations which may require the application of emergency tools to better adapt to economic challenges. Apart from Egypt, Morocco, Tunisia, South Africa and Zambia national Trade Defence Instruments (TDIs) are not well developed. This could further constrain the ambitious African plans of economic integration. The thesis concludes that, although an effective TDI system is crucial for African integration as it can provide the required protection for African infant industries and unlock the potentials of African economic integration, the current African TDI systems are not effective. This is confirmed by the limited resort to TDIs in the African continent and the general perception that an effective TDI system is not a priority on the integration agenda. The concluded T-FTA TDI legal regime is not supportive for African integration plans in the long run. Africa should envisage how to upgrade its TDI system to make better use of the tools available under the WTO to deal with unfair trade measures, including anti-dumping to face dumped imports, countervailing measures to face subsidized imports, and safeguard measures to temporarily suspend concessions in the face of surge in imports. Africa can improve its national and regional TDIs system by learning from more developed TDI systems incorporated by other economic blocks such as the EU, NAFTA, Mercosur, and ASEAN. This thesis submits that the EU TDIs system is the most suitable to the African integration objectives. This submission is made while recognising the different level of development on both sides. The thesis submits that the long-term objective of the T-FTA is to have a regional investigating authority. It draws several recommendations to enhance African TDI system by working on five main categories: (A) The strategic direction; (B) The institutional framework; (C) Enhancing engagements; (D) Application of TDIs; and (E) The supportive factors.
URI: https://repository.up.ac.za/handle/2263/60043
Keywords: Economic integration; Trade defence instruments; Unfair trade practices

Private Ordering of Exit in Limited Liability Companies: Theory and Evidence from Business Organization Contracts - Gomtsian, Suren (American Business Law Journal, 2016)
https://onlinelibrary.wiley.com/doi/10.1111/ablj.12087

Contracts Governing the Use of Websites - Mik, Eliza (Singapore Journal of Legal Studies, 2016)
With the progressive transformation of the Internet from a romanticised instrument of freedom and self-expression into a commercial platform for digital distribution, most websites must be recognised as access interfaces to a wide range of content and services. This paper examines the contracts purportedly governing the use of such content and services. It explores the difficulties of establishing legal intention in a context that is not unambiguously commercial or transactional and contrasts popular beliefs with the basic principles of contract law. It draws a clear distinction between contracts governing traditional e-commerce exchanges, such as buying books on Amazon.com, and contracts governing the very use of websites. In the latter instance, the website (ie the resources made available thereon) constitutes the subject matter of the transaction. Equal importance must be attributed to the fact that such contracts are formed on websites and to the fact that they govern their use. The website user will question the existence of a contract on the basis that he did not have an intention to be legally bound, or had no awareness that a transaction was taking place. The website operator will argue that, objectively, all prerequisites of a legally enforceable agreement have been met. The outcome of the discussion will, to a large extent, depend on whether the user’s beliefs and expectations can be regarded as reasonable and on whether it is the user or the operator who deserves the protection of the objective theory of contract.

Avoidance of a contract under the CISG - Otenga, Emongo Jean-Marc (University of Johannesburg, 2015)
Keywords: CISG; Commercial law; Contracts (International law); United Nations Convention on Contracts for the International Sale of Goods (1980 April 11)

The complex case for another hard look : transnational pharmaceutical regulation and the pedagogical role of courts - Rizzi, Marco (European University Institute, 2015)
The thesis argues for a 'pedagogical' role for courts in the US and EU in ameliorating the increasingly transnational regulation of pharmaceutical product safety through complementary monitoring of the outputs of regulatory processes. The study is divided into two parts. First, the thesis explores the regulatory institutional design in the US and EU. The parallel development of the FDA and EMA suggests that both markets have achieved consolidated domestic/regional regulatory frameworks, which do however show multiple weak spots. These vulnerabilities are aggravated by a strong push towards transnationalisation of regulatory procedures: domestic systems are now permeated by potentially disruptive exogenous elements (e.g. the ratification of transnationally negotiated protocols and increasing reliance on foreign clinical trials data). The thesis explores issues of effectiveness of safety delivery and legitimacy of rule-making processes to suggest scope for improvement in both areas. The second part considers the potential contribution of the judiciary, particularly national courts in the US and EU, to investigate whether the exercise of complementary judicial governance can enhance the effectiveness and legitimacy of an otherwise essentially closed and self-perpetuating system. A selection of cases grounds the claim that, through liability litigation, courts have the capacity to improve the safety levels delivered by regulation and thereby to contribute to output-based legitimacy of the institutional design. This claim is tested in light of acknowledged strengths and limitations of court processes and with regard to differentiating elements at the national level, particularly regarding access to justice. The concluding argument reassembles the results of the study to recommend the existing tool of domestic litigation as a response to certain vulnerabilities in pharmaceutical regulation. The 'hard look' doctrine described by Sheila Jasanoff grounds the normative claim for a 'pedagogical' role for courts, enhancing regulation beyond the outcome of isolated cases – ad adiuvandum rather than contra.
Accepted: 2015-11-04T16:35:28Z
Keywords: Drugs; European Union countries; Pharmaceutical industry; Pharmaceutical regulation; Pharmaceutical right; United States

Public-private cooperation in transnational regulation - Schmidt, Rebecca (European University Institute, 2015)
This thesis examines the emergence of transnational regulatory cooperation between public and private actors. It inquires why a private regulator and an international organisation may enter into a cooperation agreement in order to regulate particular issues, and what this tells us about the relationship between ‘expertise,’ ‘authority’ and ‘legitimacy’ in particular domains of global governance. The argument put forward in the thesis is that different types of regulators cooperate because, in an unsettled global space with no hierarchical framework, it is necessary for them to acquire sufficient authority to secure compliance with their regulatory agenda. In order to acquire and maintain such authority, regulators must be perceived as legitimate and their regulation as effective. Cooperation can open venues for participation and deliberation and for the exchange of necessary competences (particularly expertise); and thus ultimately can help regulators establish and strengthen their authority. Another important finding of this research is that cooperation can develop into more long-lasting network structures. These networks are often of a multi-level nature. As such, they traverse local, national, and international spaces. The thesis then develops the idea of ‘networks of constitutionalization’ to describe the observation that bilateral arrangements as examined here generate ordering effects which extend beyond the two parties. Consequently they become the basis for norm creation and adoption for different types of actors located in the networks formed around the issue area. Thus, even in pluralistic structures, eventually a certain kind of constitutionalization can emerge putting into question sharp divisions between ‘pluralist’ and ‘constitutionalist’ interpretations of a developing global (legal) order. This work also encompasses two case studies: the ISO 26000 process, whereby the ‘private’ technical standard setter ISO concluded separate cooperation agreements with the ILO, the OECD and the UN Global Compact; and a case study on ‘Sport and Environment’ that focuses on the long-standing cooperation between the IOC and the UN Environmental Programme.
Accepted: 2015-04-16T14:24:52Z
Keywords: International Law; Law and Globalization

Substantive equality, affirmative action and the alleviation of poverty in South Africa : a socio-legal inquiry - Katiyatiya, Luyando Martha (Stellenbosch University, 2014)
Substantive equality is a constitutional imperative, hence the need for strategies that attempt to realise it for the sake of genuine social reconstruction. The principle of equality runs through all other rights in the South African Constitution. Be that as it may, equality is an elusive concept, which makes its achievement an ambitious task. Nonetheless, there are strategies that attempt to bring to the fore the ‘substance’ of the concept in order to ensure the actual realisation of socio-economic benefits. Such strategies include, among others: social security, education, economic empowerment, skills development and affirmative action. This study will focus on the latter of these strategies, namely affirmative action. Although affirmative action is practised around the world, one of the (many) criticisms of the policy is that it fails to bring about substantive or structural change. In other words, it may change the racial and gender composition of the classroom or the workplace, but does not address the challenges that cause the disadvantages of marginalised groups in the first place. It is arguable that affirmative action has increased inequality in South Africa by benefiting the apex of the class structure and not the majority of the population living in abject poverty. This study develops a theoretical analysis of the link between status (race, sex and ethnicity) and socio-economic disadvantage, and the central question that the study addresses is the following: How can the policy of affirmative action be redesigned to ensure that it benefits the socio-economically disadvantaged? A secondary question that is investigated is whether affirmative action can contribute to the development of human capacities in the context of poverty alleviation. It is arguable that substantive equality facilitates the adoption of strategies (such as affirmative action) to address socio-economic inequality, poverty and social exclusion. The research suggests that a paradigm shift is necessary in order to reconceive of affirmative action as a policy that does not only focus on ensuring ‘equitable representation’ of disadvantaged groups in the workforce or the classroom, but also provides for the development of human capacities. This can be achieved if one adopts an expansive view of affirmative action and if one utilises class as one of the numerous criteria for determining the beneficiaries of the policy.
URI: http://hdl.handle.net/10019.1/86607
Keywords: Affirmative action programs; Equality before the law; Politics and government; Public welfare; Social conditions; South Africa

Bringing Formal Business Laws to Cameroon’s Informal Sector: Lessons and Cautions from the Tax Law Example - Dickerson, Claire Moore (Washington University Global Studies Law Review, 2014)
A substantial majority of non-agricultural workers in a developing country such as Cameroon engage in legal businesses below the governmental radar, that is, in the informal sector. Because that segment of the Sub-Saharan economy is critical to subsistence within the region, and because the financial crisis has expanded the informal sector in the Global North, developing economies’ experience with the informal sector is of world-wide relevance. Formal business laws do exist in the formal sector; however, trying to move informal-sector workers to the formal sector where these laws already offer some protection can disrupt the entrepreneurs’ ability to sustain themselves, and to contribute to the national economy. A pilot study in five Cameroonian markets is thus of general interest when it reveals that entrepreneurs there do not benefit from formal business laws, which in turn limits their ability to borrow and their willingness to lend. The same study also suggests that tax literature has interesting, non-coercive strategies to improve tax compliance in ways that may be applicable to facilitating the introduction of formal business laws to the informal sector, instead of forcing informal-sector workers into the formal sector. The tax-morale literature recommends deploying strategies of reciprocity, in addition to providing public goods and services—strategies that encourage compliance—instead of using governmental power to extract tax payments. Similarly, tax-based strategies can apply to business laws while informal-sector workers remain in the informal sector, even though the government’s posture vis-à-vis commercial actors is less direct than vis-à-vis taxpayers. The experience of Cameroon’s informal sector with formal tax law thus provides important insights on steps within the government’s control that would not only improve tax compliance, but would also bring formal business laws and their transaction-cost-reducing potential to the informal sector. The pro-business strategy is to apply tax-morale learning, which calls for government authorities to enter into a reciprocal relationship— respectful and communicative—with private parties and to focus on investing in basic infrastructure.

Legal aspects of privately financed infrastructure projects (PFIPs) in China: the case for international standards - Liang, Shuang (University of Leeds, 2013)
This thesis discusses the reform and improvement of Chinese legislation on Privately Financed Infrastructure Projects (PFIPs), to develop the PFIP model in China, under the protection of Chinese laws, so that its implementation in China may reach international standards. Existing Chinese laws are found to be insufficient in reducing risks to PFIPs because of certain shortcomings. Therefore, it is necessary to reform and improve Chinese legislation on PFIPs, to prevent their failure. The Legislative Guide and Model Provisions drafted by UNCITRAL are treated as the international standards to guide Chinese legislation reform on PFIPs. Other countries’ laws on PFIPs provide supplementary reference. This thesis addresses its aim in four steps: First, the current Chinese legislative and institutional framework on PFIPs is reviewed, with discussion on establishing a more appropriate legislative and institutional framework, to facilitate the development of PFIPs in China through the principles of transparency, fairness, long-term sustainability and the elimination of undesirable restrictions. Second, Chinese laws on the concessioner selection procedure in PFIPs are reviewed, with discussion on possible improvements to the laws to achieve international standards of fairness and transparency. Third, current Chinese laws and policies which affect the various contracts involved in PFIPs are reviewed, with discussion on these may be improved to achieve international standards. Fourth, the PFIP dispute settlements that may be used in China are reviewed, with discussion on the necessity to remove certain undesirable restrictions in relevant Chinese laws. Following the rapid rise in the practical use of PFIPs in China, this thesis offers a strong theoretical basis for suggesting a reform of Chinese legislation on PFIPs. It also provides a general basis for any national reform of laws on PFIPs in any other countries.

Law harmonization and local specificities – a case study: OHADA and the law of contracts - Fontaine, Marcel (Uniform Law Review, 2013)
Unifying or harmonizing the laws of different countries means replacing, to respective degrees, the existing national laws with common rules.1 The merits of law unification or harmonization may seem to be obvious. They have been repeatedly described. Law diversity is an obstacle to trade between countries. Engaging in a commercial operation with a partner of another legal system immediately raises the question of which law will govern the relationship, with the consequence that, for one of the parties, the contract will be subject to unfamiliar rules (perhaps even for both parties if the law of a third party is determined to be applicable).

The Problem of the Taxation of Internet Transactions - Asada, Dominic (Current Jos Law Journal, 2013)
Accepted: 2017-08-16T12:06:13Z

Statutory regulation of forced sale of the home in South Africa - Steyn, Lienne (University of Pretoria, 2012)
The home of a debtor has never enjoyed specific statutory protection against forced sale in the individual debt enforcement and insolvency procedures in South Africa. In Jaftha v Schoeman and Others; Van Rooyen v Stoltz and Others (2005 (2) SA 140 (CC)) and Gundwana v Steko Development CC and Others (2011 (3) SA 608 (CC)), the Constitutional Court recognised that in the individual debt enforcement process execution against a debtor's home, even where it has been mortgaged in favour of a creditor, may constitute an unjustifiable infringement of the right to have access to adequate housing, provided by section 26 of the Constitution. The effect of these decisions is that, in every case in which a creditor seeks to execute against a person's home, a court must consider "all the relevant circumstances" to determine whether execution is justifiable, in terms of section 36 of the Constitution. The absence of a properly constructed framework, incorporating clear substantive and procedural requirements, within which these recently established principles must be applied, has led to divergent approaches in the courts and a lack of clarity regarding circumstances in which execution against a debtor's home will be permitted. Further, courts have not considered the impact of section 26 and other rights on the position where a debtor's home is realised by the trustee of an insolvent estate in terms of the Insolvency Act 24 of 1936. This has given rise to a number of unanswered questions as well as to a lack of predictability that potentially hold adverse consequences for bond finance, commerce, and the economy generally. The need to balance the competing interests emphasises the necessity for a coherent contextual framework within which forced sale of a debtor's home may occur. This thesis examines issues surrounding forced sale of a debtor's home in South Africa. It compares the position in other legal systems and suggests mechanisms and an appropriate method, or process, for inclusion in statutory provisions to regulate the forced sale of a debtor's home in both the individual debt enforcement and insolvency procedures in South Africa.
Keywords: Forced sale; Vente forcée

Theory of Choice of Law and Party Autonomy - Basedow, Jürgen (SungKyunKwan Law Review, 2012)

The Business Trust and its role as an entity in the financial environment - Nel, Ebenhaéser Cornelis (Nelson Mandela Metropolitan University, 2012)
The trust figure in South Africa has undergone an interesting process of evolution during the last century – from a mere gratuity or private tax evasion tool to a proper family protection, business entity, investment, and structured finance vehicle. Its flexibility and multi-functionality positioned the trust as an ideal legal institution for many innovative ideas in the search for holistic business structures, economic empowerment transactions, general estate planning and risk protection initiatives, and ultimately, its application as financial instrument and structured finance entity. The development of both traditional and synthetic securitisation schemes in South Africa has been investigated, with some emphasis on the application of the special purpose institution, which may be in trust form. It is submitted that the application of the trust figure has developed without any significant contribution from the local legislator. A sound legal and regulatory framework is crucial for the creation of a strong future environment for legal and financial vehicles. The question is, however, whether the current South African legal framework for the application of the business trust, and also as a vehicle for financial instruments, is adequately sound and robust in light of the standards set in the international business and financial environment. It is submitted that the hybrid nature of the South African legal landscape is conducive for the development of sound legal systems in an ever-changing legal and economic reality. It is further submitted that in the development of proper legal frameworks, South Africa should position itself particularly in its context as a Southern African developing democracy. The South African trust development is compared with that of some foreign jurisdictions as well as with international conventions and treaties of relevance. Some recommendations for necessary changes are made and it is submitted that such future development of the trust figure should not take place haphazardly, but within the context of a structured regulatory model
NMU Archives and Exhibition Centre
Keywords: Asset-backed financing; Corporations; Taxation; Trusts and trustees

Codification of Contract Law: Some Lessons From History - Swain, Warren (University of Queensland Law Journal, 2012)

A Brief Analysis of the Disputes Arising from China-African Civil and Commercial Transactions - Zhu, Weidong (Journal of Cambridge Studies, 2012)
Keywords: Arbitrage; Arbitragem; Arbitration; China-African civil transactions; China-African commercial transactions; Disputes; Litigation

A Comparative Study of Contract Formation and Breach of Contract and Liability in China and OHADA Space Contract Laws - Traoré, Moussa Sékou; Xiao, Yongping (Journal of Politics and Law, 2011)
Chinese politicians and businessmen and their African counterparts are improving economic and commercial relations between them. This manifest interest of partnership needs a legal framework which guarantees equal and fair advantages to both parties. To reach this global aim, China and Africa must develop their collaboration in the domain of law. In the 80s China has adopted laws to reflect the country's economic and social demands such as Economic Contract Law (1981), Foreign Economic Contract Law (1985), General Principles of Civil Law (1987). Now, to better facilitate economic growth the National People's Congress (NPC) has unified China's various national specialized contract laws to obtain the “Uniform” Contract Law 1999. OHADA is a system that aims the harmonization of business law in Africa. This study aims to compare the two systems contract formation, breach of contract and liability for breach in order to have a legal frame more appropriate for business between China and this part of African Continent.

South African anti-dumping law and practice : a juridical and comparative analysis of procedural and substantive issues - Sibanda, Omphemetse Stephen (North-West University, 2011)
This thesis addresses issues of anti-dumping law and practice from a critical and juridical analysis position. In particular, the thesis seeks to determine whether the South African anti-dumping regime is compliant with the anti-dumping regime of the World Trade Organization (hereafter WTO), and to consider possible solutions for addressing instances where the South African law is not WTO compatible. The thesis departs from the hypothesis that the WTO merely requires functional equivalence of the implementation of national legislation on anti-dumping, and not the verbatim adoption of WTO jurisprudence and relevant provisions of the Agreement on the Implementation of Article VI of the General Agreement on Tariffs and Trade of 1994 (hereafter URAA), into the legislation of State Parties. Some of the provisions of the URAA are not completely clear, and are cast in convoluted and complicated technical jargon, leaving loopholes that may be justifiably exploited by State Parties. The study in this thesis was achieved through the critical analysis of legislation and relevant legal documents, case law and contemporary literature. The primary research paradigm used in this study is interpretive and analytical, which is the same as qualitative research methodology. The legal comparative research method, with a historical component, also played an important role in this study. The literature study undertaken and the critical analyses made of the South African anti-dumping regime show mixed findings. The South African antidumping regime was found to have both positive aspects and problematic aspects when compared with WTO regulations. Some of the critical areas of the South African anti-dumping regime are WTO compatible whilst others are not. In some areas the South African anti-dumping regime has adopted functionally equivalent provisions to the provisions of the WTO law. However, the practice of the International Trade Administration Commission (ITAC) is sometimes fraught with inconsistencies. The compatibility of the South African anti-dumping system with the WTO regime came close to being examined by the WTO on 1 April 1999 in the dispute of South Africa - Anti-dumping Duties on the Import of Certain Pharmaceutical Products from India based on allegations that the method for calculating normal value used by the ITAC was found to be inconsistent with the URAA. Similarly, the conformity of the procedures and findings of the International Trade and Administration Act (ITAA) in anti-dumping cases came under attack in the cases of Algorax v The International Trade Administration Commission and others, and Scaw v The International Trade Administration Commission and others, respectively. Finally, the thesis ends with recommendations in response to the challenges identified and key submissions made throughout the analysis. Key recommendations include the broadening of the concept of interested parties to include registered trade unions and trade union federations; introducing an explicit and mandatory "public Interests" provision to ensure that South Africa's anti-dumping administration is free from political trappings in the form of the involvement of the Minister of Trade and Industry; introducing the new section 31 bis of the ADR in order to allow the initiation of anti-dumping petitions by a registered trade union or trade union federation; providing procedural guidelines for self-initiation of anti-dumping petitions by the ITAC; increasing transparency in anti-dumping proceedings and enquires; setting realistic time-lines for all anti-dumping processes and ensuring compliance with the same; improving the institutional and functional capacity of the ITAC; amending section 18.3 of the ADR to allow search and seizure operations pursuant to the provisions of the Criminal Procedure Act 51 of 1977 and the Customs Act; having a clear provision on verification visits confidentiality and a clear provision on producer knowledge; introducing a clear provision in the ADR dealing explicitly with zeroing pursuant to Article 2.4.3 (ii) of URAA; and the introduction of duty refund procedures. It is hoped that the recommendations made in this thesis, which are in the form of suggested legislative interventions required to upgrade certain areas of South African anti-dumping law and practice to be fully WTO compliant, will influence the introduction of suitably crafted anti-dumping legislation in South Africa. It is further hoped that the thesis will become an invaluable source of information for practitioners and students, and a critical source on the best practice for the imposition and implementation of anti-dumping measures. Moreover, the thesis will add to the body of academic writing on South African anti-dumping law.
Keywords: Antidumping duties; Dumping (International trade); South Africa

Trends on the Harmonization of Contract Law in Africa - Mancuso, Salvatore (Annual Survey of International & Comparative Law, 2010)

A critical evaluation of the interaction between sport and law in South Africa - Louw, André Mouton (Stellenbosch University, 2010)
This dissertation contains an evaluation of the interaction between law and sport in South Africa. The evaluation includes description of the main areas where laws (in the form of the common law, legislation and the relevant provisions of the Constitution of the Republic of South Africa, 1996) apply to sport, in the contexts of both amateur sport and the fast-developing professional sports industry. Apart from such descriptive content, the dissertation will also critically evaluate the appropriateness of the relevant laws and their application in the often atypical context of sport, as well as the courts' treatment of the relevant legal issues. In the process of providing such critical evaluation, and where relevant, the author includes a comparative analysis of the treatment of relevant legal issues in other jurisdictions (most notably the United Kingdom and European Union, which are especially relevant in light of the application of the 'European model' of sports governance and regulation, which applies to the major sporting codes in South Africa). In particular, the author critically evaluates the following aspects of the South African jurisdiction's treatment of the application of law to sport: - The South African system of public regulation of sport by the State (and, specifically, the issue of the race-based transformation of sport, which involves an apparent government-driven agenda and is unique to the South African jurisdiction); - The courts' treatment to date of the susceptibility of the conduct of sports governing bodies to judicial scrutiny (and of the nature of such bodies as voluntary associations); - Various aspects related to the application of employment laws to the employment of professional athletes in team sports; - The application of common law remedies for breach of contract in the professional sports employment context; - The potential application of the restraint of trade doctrine (in, as the author suggests, an extended_ form) in the context of the freedom of movement of professional athletes; The apparently unsatisfactory state of current South African law in respect of legal protection against commercial misappropriation of aspects of the persona of famous athletes (i.e. in the context of 'image' -or-,'publicity' rights as recognized in certain other jurisdictions); and - An evaluation of the extensive protection (especially in the form of specific legislation in South Africa) against ambush marketing of major sporting events. The author includes some concluding observations regarding the state of South African sports law as compared to other jurisdictions, as well as some comment on expectations for the future development and potential importance of the South African domestic jurisdiction in the application of law to sport.
URI: http://hdl.handle.net/10019.1/49490 There are three other contributors to this work numbering 15 p. in total.
Keywords: Comparative law; European Union; South Africa; Sports; United Kingdom

Business law transplants and economic development: an empirical study of contract enforcement in Dakar, Senegal - Paquin, Julie (McGill University, 2010)
La création d'environnements attrayants pour les investisseurs est récemment devenu une priorité pour les spécialistes du développement, qui conseillent aux pays en voie de développement d'adopter les « meilleures pratiques » d'affaires utilisés dans les pays développés. Bien qu'on reconnaisse que le transfert de modèles juridiques d'un pays à un autre entraîne souvent des résultats décevants, la question du niveau de compatibilité requis entre les modèles transférés et le pays importateur est le plus souvent ignorée ou considérée comme une question technique relevant de la compétence des professionnels du droit locaux. Dans ce processus, pratiquement aucune place n'est faite au point de vue des utilisateurs finaux des nouvelles normes et institutions. La présente thèse se fonde sur une étude empirique de l'impact de la réforme du droit des affaires relativement en matière d'exécution des contrats. Dans une première partie, les hypothèses sur lesquelles les réformes actuelles se fondent sont examinées à la lumière de contributions provenant de divers champs disciplinaires. Divers facteurs considérés comme expliquant les effets limités des réformes entreprises jusqu'à présent sont présentés. La deuxième partie analyse le contenu de 30 entretiens en profondeur réalisés auprès de petites et moyennes entreprises de Dakar, Sénégal. Les entretiens révèlent que les PMEs dakaroises font preuve d'une grande flexibilité dans l'exécution de leurs contrats d'affaires, et que la qualité des institutions juridiques et judiciaires joue un rôle peu important dans les décisions qu'ils prennent à cet égard. L'environnement général dans lequel elles opèrent, qui se caractérise par la présence de contraintes financières importantes, un haut niveau d'inceritude et une grande interdépendance entre les entreprises, constitue le facteur le plus important pour expliquer le comportement des entreprises. La troisième part
https://escholarship.mcgill.ca/concern/theses/gm80hv75c
Keywords: Business law; Contract enforcement; Economic development; Senegal

A Critique of Trade Disputes Settlement Mechanism in Nigeria: 1968 to 2004 - Anyim, Francis Chukwudike (University of Lagos, 2009)
Full texts attached
https://ir.unilag.edu.ng/handle/123456789/4419
Keywords: Conflict Manifestation; Labour market research; Marxist Perspective; Process of Collective Bargaining; Strike and its effect

E-Commerce and Mobile Commerce in South Africa: Regulatory Challenges - Jobodwana, Z. Ntozintle (Journal of International Commercial Law and Technology, 2009)
E-commerce refers to all forms of commercial transactions that involve individuals and organizations based on the electronic processing of data. Mobile commerce (M-commerce) is the buying and selling of goods and services using mobile telephones or personal digital assistants (PDA). M-commerce is emerging in Africa and South Africa especially as either a complement or an alternative to e-commerce as originally conceived, though there are arguments that mobile telephone technology â€œm-commerceâ€ will surpass â€œe-commerceâ€ as the method of choice for digital commerce transactions. This paper identifies the challenges in adopting e-commerce/m-commerce practices for economic development and competition in International trade. The liberalisation of the telecommunications sector on which e-commerce and m-commerce practices depend is being given priority by the majority of African governments. Despite advances in e-commerce and m-commerce practices in Africa, the growth of e-commerce and m-commerce has been slow. Impediments include low levels of internet penetration and limited communication infrastructure. To meet this problem, the UN adopted through the UN Commission on International Trade (UNCITRAL), Model Law on E-Commerce to help in the harmonisation of e-commerce/m-commerce related laws. Challenges are identified and recommendation made on how to improve the regulatory framework and create an environment conducive to investment and economic development.
https://www.neliti.com/publications/28783/

Status Ambiguity and Conflict in the Market - Tan, David (Emory University, 2009)
My main theoretical contention is that status hierarchies provide a source of guidance to firms for resolving disputes. A status hierarchy implies a system of deference rules among firms. When disputes arise, deference rules can provide a basis for shared expectations and protocols of conduct about how technical ambiguities should be resolved. In many contexts, technical merit is difficult to assess. However, deference rules can operate as social conventions to which firms default, helping to align potentially incompatible expectations. Within this general framework, my dissertation examines how competitors in the semiconductor industry manage uncertain and frequently overlapping patent rights. In practice, patent rights are highly imperfect legal instruments when it comes to demarcating each firm's contributions to innovation in the industry. Patent disputes arise because of the ambiguity this creates about how much of the collective market returns to innovation each firm is entitled to receive. Despite the prolific patenting and propensity for disputes, the industry has remarkably not ground to a halt from runaway litigation. Litigation events, while significant, are rare. I suggest that this degree of order is, at least partly, attributable to status processes. Status can operate as a stabilizing force in the market, helping to generate orderly competition in the face of disputes. To examine whether this is the case in the semiconductor industry, I theorize that disputes are less easily resolved when the parties involved face greater status ambiguity, i.e. are less clearly differentiated from one another in status. Under status ambiguity, deference rules lose the rule-like, universal quality that makes them persuasive in resolving disputes. This has two consequences. First, firms facing low status ambiguity are less likely to be involved in patent litigation than are firms facing high status ambiguity. Patent litigation events represent failures to resolve patent disputes out of court. Second, firms facing low status ambiguity increase their product line sizes more than do firms facing high status ambiguity. The threat of difficult-to-resolve patent disputes represents a cost that can deter firms from bringing products to market.
Permanent URL: https://etd.library.emory.edu/concern/etds/9g54xj191?locale=en
Keywords: Litigation; Patent; Semiconductor; Status

On formation of a share company in Ethiopia - Tesfay, Seyoum Yohannes (Journal of Ethiopian Law, 2008)
Keywords: Attributes; Ethiopian law; Formation; Share company

The Commercial Lease: Property or Contract - Brock, Jason; Phillips, Jim (Alberta Law Review, 2001)
The commercial lease has historically been treated as a conveyance of an interest in land which creates a property-based relationship between the lessor and lessee, despite the fact that the relationship is created by contract and could be seen as a contract for the ongoing use of the land. Some Canadian cases, however, have applied "partial contractualization " — using both property and contract rules and concepts to interpret leases. The article examines the historical development of the lease and its treatment in Canadian courts, as well as in other common law courts. The authors argue that the property/contract hybrid should be eliminated in favour of "complete contractualization " — using pure contract principles to interpret the commercial lease. The article points out how contract principles would serve the parties to the lease just as well, or better, than property principles and offers solutions for the anticipated problem area of security of tenure for the tenant.

Restraint of trade at common law - Dempster, Hamish Leslie (University of Auckland, 1997)
This is a collection of essays about the restraint of trade doctrine as laid down in the courts of the United Kingdom and the British Commonwealth. Generally, I will not give an account of the restraint of trade doctrine in the United States of America, for even although each individual state (apart from the civil jurisdictions California and Louisiana) and the federation itself, has a common law system, for reasons peculiar to those jurisdictions, the restraint of trade case law there has become so vast and so confused as to be unsuitable for my purposes. More importantly, however, the common law restraint of trade doctrine in the United Kingdom and the British Commonwealth has been laid down by courts without any significant consideration of the state of the law in the United States. Davies v Davies (1887) 36 Ch D 359, 370 by contrast, the period during which the Privy Council operated as a supra national court of final appeal has resulted in considerable harmony in the doctrine within the British Commonwealth. Even now the House of Lords is influential in Australia and Canada and the influence is increasingly reciprocal. By way of an exception I will discuss the purposes of the anti-trust legislation in the United States. This is necessary because I intend to show that the common law restraint of trade doctrine was not able to be, and was never intended to be, a means of regulating the economy in contradistinction to the United States anti-trust legislation and related legislation in the British Commonwealth. This account is not merely a description of the law relating to the restraint of trade doctrine although I do purport to describe the law. There are other accounts of the restraint of trade doctrine which do that well. Accounts of the restraint of trade doctrine include: Matthews & Adler, The Law Relating to Covenants in Restraints of Trade (London, 2nd ed 1907); Sanderson, Restraint of Trade in English law (London, 1926); Heydon, The Restraint of Trade Doctrine (London, 1971); Trebilcock, The Common Law of Restraint of Trade; A Legal and Economic Analysis (Toronto, 1986); Dean, The Law of Trade Secrets (Sydney, 1990); Mehigan & Griffiths, Restraint of Trade and Business Secrets: Law & Practice (London, 2nd ed 1991); Holdsworth, History of English Law IV (3rd ed, 1945) 343-54, 373-9; VIII (2nd ed, 1937) 56-42. There are other, less detailed accounts in contract law textbooks. The purpose of this dissertation is to describe aspects of the doctrine as it developed between the medieval period and the twentieth century and then to use that account as a basis for an analysis of how the law has taken a number of paths during the twentieth century which cannot be justified by the rules and their justifications which existed in the law prior to that time. Such a development has had important consequences for the restraint of trade doctrine and even the law in general, most of which have been detrimental. I do not intend to give a continuous historical narrative covering the whole of the doctrine. The history has been described before. For example, I do not intend to give a discrete account of the process by which the absolute rule against general restraints of trade gave way to the rule of reason, although I do mention this process where relevant for other purposes. The history, so far as it is relevant, is integrated into each chapter. I will argue that historically the restraint of trade doctrine was a rule or complex of rules, of a certain form and content. The form and content of the rule are important because they bear on the meaning of the class term "restraint of trade" which is an element of the rule. The meaning of that term began to change around the year 1890. Beginning first with certain classes of trade combination, courts began to classify as restraints of trade covenants which did not in fact restrain trade. Then the courts similarly treated the exclusive dealing contract and certain forms of property transaction. Another trend in the law which added to the confusion about the meaning of restraint of trade was the failure by the courts to make definitive findings one way or another as to whether a particular covenant was in restraint of trade. The courts were then faced with a dilemma. The law required a court to refuse to enforce a covenant in restraint of trade unless the covenantee could justify the restraint by presenting evidence to the court from which the courts could assess whether or not that particular restraint was within the reason for the restraint of trade doctrine or not. Such considerations were entirely inapt in the case of covenants which, in accordance with the traditional view, did not restrain trade. Yet if the courts did not validate these contracts, catastrophic consequences would have followed for the parties to such contracts and, indeed, to contract as an institution. To solve the dilemma the courts began to interpret the famous statement of the restraint of trade doctrine by Lord Macnaghten in Nordenfelt v Maxim Nordenfelt Guns & Ammunition Co [1894] AC 535, 565 (HL) literally, rather than contextually. Ultimately this has resulted in the obscuring of the rule underlying the restraint of trade doctrine itself. There were many minor confusions along the way. It is important that the doctrine is coherent and its use consistent with its justifications because it is still a fruitful cause of legal change. In the last year the force of the rule has caused a radical restructuring of Association Football in Europe Bosman’s case. The rule has even penetrated the collective consciousness of the community at large. The broad thrust of the development and the detail will be outlined in the next thirteen chapters.

A behavioural study of the rental housing market in Ibadan, Oyo State of Nigeria - Asaju, Adebakin Simeon (Obafemi Awolowo University, 1994)
Keywords: Besoins en logement; Composition du ménage; Household composition; Housing market; Housing needs; Ibadan; Logement locatif; Marché du logement; Nigeria; Oyo State; Rental housing; État d'Oyo

Trade and justice - Robe, Jean-Philippe (European University Institute, 1992)
Keywords: Intergovernmental fiscal relations; Justice; Trade